Playing Dystopia - Farca, Gerald (transcript Verlag, 2024)
Video games permeate our everyday existence. They immerse players in fascinating gameworlds and exciting experiences, often inviting them in various ways to reflect on the enacted events. Gerald Farca explores the genre of dystopian video games and the player's aesthetic response to their nightmarish gameworlds. Players, he argues, will gradually come to see similarities between the virtual dystopia and their own ›offline‹ environment, thus learning to stay wary of social and political developments. In his analysis, Farca draws from a variety of research fields, such as literary theory and game studies, combining them into a coherent theory of aesthetic response to dystopian games.